Synthesis and properties of blue luminescent bipolar materials constructed with carbazole and anthracene units with 4‐cyanophenyl substitute at the 9‐position of the carbazole unit. (29th January 2018) - Xie, Pengbo; Yuan, Ningning; Li, Shanji; Ouyang, Ying; Zhu, Yongju; Liang, Hui
Abstract: With carbazole and p ‐cyanobromobenzene as raw materials, 4‐(3, 6‐di (anthracen‐9‐yl)‐9H‐carbazol‐9‐yl)benzonitrile (DACB) and 4‐(3, 6‐bis(anthracene ‐9‐ylethynyl)‐9H‐carbazol‐9‐yl)benzonitrile (BACB) were synthesized through the Suzuki coupling reaction and the Sonogashira coupling reaction, respectively. These structures were characterized using 1 H nuclear magnetic resonance (NMR), elemental analysis and mass spectrometry. Their thermal properties, ultraviolet–visible (UV‐vis) absorption, fluorescence emission, fluorescence quantum yields and electrochemical properties were also investigated systematically. In addition, a electroluminescence (EL) device was made with BACB as the emitting layer and performance of the EL device was studied. Results showed that: (1) the temperature points with 5% and 10% of DACB weight loss were 443°C and 461°C, respectively, and were 475°C and 506°C with BACB weight loss of 5% and 10%, respectively. When the temperature was 50−300°C, no significantly thermal transition was observed which suggested that they had excellent thermal stability. (2) DACB and BACB had single emission peaks at 415 nm, and 479 nm with fluorescence quantum yields of 0.61 and 0.87, respectively, indicating that both compounds could emit strong blue light. (3) According to electrochemical measurement on BACB and DACB, their gaps were 3.07 eV and 2.76 eV, respectively, which further showed that these two compounds were very stable and acted as efficient blue light materials. (4) The turn‐on voltage of the device was 5 V, and the device emitted dark blue light with Commission Internationale de L'Eclairage (CIE) coordinates of (0.157, 0.079).